Wooden Tserkvas of the Carpathian Region in the UNESCO World Heritage List. Common Problems and Local Solutions - Herych, Volodymyr (Regional Barometer. Analyses & Prognoses, 2013)
This year we have managed to implement a joint international project aimed at including the best Carpathian wooden tserkvas of the Polish-Ukrainian borderland in the UNESCO World Heritage List. Each of the 16 objects has its own problems which are illustrated on the example of the Tserkva of the Holy Trinity. Its rich history, the urban context, the environment and the period of the building erection, its design and equipment, cultural and religious backgrounds are the basis of today’s work on the UNESCO object. Legal, state and local regulations create some opportunities for its preservation and best use. A very important element of the church maintenance is monitoring which should be provided by heritage protection authorities. All mentioned steps should provide, in particular, the popularization of the object, development of tourism and growth of the attractiveness of town or village. Each church can be a place of stimulating investment and development of the local economy, as well as basis for creating projects regionally significant.